2017
DOI: 10.1016/j.diabres.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemoglobin glycation index and hepatic steatosis in non-diabetic individuals

Abstract: Hemoglobin glycation indexHepatic steatosis Non-enzymatic protein glycation A B S T R A C TAims: Hemoglobin glycation index (HGI), which is the difference between the observed value of HbA1 and the predicted HbA1c based on plasma glucose levels, represents a measure of the degree of non-enzymatic glycation of hemoglobin and it has been found to be positively associated with diabetic complications. Herein we investigated whether HGI is associated with hepatic steatosis and related biomarkers in subjects without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…However, until now, only a single study has investigated the association between HGI and NAFLD. In this study of 1120 nondiabetic, white subjects, a high HGI was associated with a 1.6‐fold increase in the risk of hepatic steatosis after adjusting for age, sex and BMI . In agreement with these data, the current study showed that a high HGI was associated with a 1.56‐fold increased risk of NAFLD, after adjusting for factors such as TG, HDL‐C, alcohol intake, hsCRP, HOMA‐IR, AST, ALT and FPG, in addition to age, sex and BMI.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, until now, only a single study has investigated the association between HGI and NAFLD. In this study of 1120 nondiabetic, white subjects, a high HGI was associated with a 1.6‐fold increase in the risk of hepatic steatosis after adjusting for age, sex and BMI . In agreement with these data, the current study showed that a high HGI was associated with a 1.56‐fold increased risk of NAFLD, after adjusting for factors such as TG, HDL‐C, alcohol intake, hsCRP, HOMA‐IR, AST, ALT and FPG, in addition to age, sex and BMI.…”
Section: Discussionsupporting
confidence: 87%
“…In this study of TA B L E 3 Risk of NAFLD by ultrasonography according to HGI quartile 1120 nondiabetic, white subjects, a high HGI was associated with a 1.6-fold increase in the risk of hepatic steatosis after adjusting for age, sex and BMI. 9 In agreement with these data, the current study showed that a high HGI was associated with a 1.56-fold increased risk of NAFLD, after adjusting for factors such as TG, HDL-C, alcohol intake, hsCRP, HOMA-IR, AST, ALT and FPG, in addition to age, sex and BMI. To the best of our knowledge, this is the first report to investigate the relationship between HGI and NAFLD in a nondiabetic Asian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome these disadvantages, in 2002, Hempe et al developed a mathematical method which termed hemoglobin glycation index (HGI) to quantify the disparity between measured HbA1c and predicted HbA1c [15,16]. Nowadays, a few articles have been reported studying the relationship between HGI and nondiabetic individuals [17][18][19]. Obviously, HGI has been used to represent the nonenzymatic protein glycation, which is known to play a key role in the pathogenesis of NAFLD [20,21].…”
Section: Introductionmentioning
confidence: 99%